Implementation of IoT based smart classroom: Room occupancy estimation, automatic seat allocation and environment monitoring - Hassan, Rakin; Salauddin, Sadia (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.